2015
DOI: 10.1016/j.clay.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the synthesis parameters of mechanochemically prepared CaAl-layered double hydroxide

Abstract: a b s t r a c tIn this work, not so commonly used methods, manual grinding and milling, were applied in an attempt of preparing phase-pure CaAl-LDH (CaAl-layered double hydroxide). For manual grinding a mortar and a pestle and the components with some added water or NaOH solution were used. Milling was a two-step procedure: dry milling was followed by milling in the presence of minute (and controlled) amount of water. The thus prepared samples were characterised by X-ray diffractometry (XRD) and scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Ca-Al LDH synthesised in the presence of a carbonate source formed more readily when compared to that synthesised with no CaCO 3 . Previous studies have shown that Ca-Al LDH and katoite (tricalcium aluminate) can result when reacting Ca(OH) 2 and Al(OH) 3 in the absence of an additional phase or carbonate source, with little to no LDH formation occurring at times [11,21,29]. Studies have also shown that, upon the addition of a third phase such as CaCO 3 or CaCl 2 •2H 2 O LDH, formation occurs more readily with little to no katoite formation.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Ca-Al LDH synthesised in the presence of a carbonate source formed more readily when compared to that synthesised with no CaCO 3 . Previous studies have shown that Ca-Al LDH and katoite (tricalcium aluminate) can result when reacting Ca(OH) 2 and Al(OH) 3 in the absence of an additional phase or carbonate source, with little to no LDH formation occurring at times [11,21,29]. Studies have also shown that, upon the addition of a third phase such as CaCO 3 or CaCl 2 •2H 2 O LDH, formation occurs more readily with little to no katoite formation.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…The most common types of mechanochemical synthesis techniques include single-step or one-pot grinding [5,6], mechano-hydrothermal synthesis [7][8][9][10] and two step grinding. Two-step grinding can consist of an initial grinding step followed by an additional treatment step or a second grinding step [11][12][13]. Grinding of raw materials can be conducted wet, dry or as a paste.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Although LDHs are less frequent than the cationic clays in nature, their synthesis is simple even in large amount and various methods are available. [27][28][29][30][31][32] The structure of the LDHs is based on Mg(OH) 2 (brucite) of octahedral coordination around the metal ions. The Mg 2+ can be substituted with trivalent cations (e.g., Al 3+ and Fe 3+ ) of similar coordination properties.…”
Section: Introductionmentioning
confidence: 99%
“…Ferencz et al [37] attempted to manufacture Ca-Al LDH by manual grinding and ball milling of Al(OH) 3 and Ca(OH) 2 . The manual milling operation failed to produce Ca-Al LDH, but the two-step milling process gave a pure phase of Ca-Al LDH.…”
Section: Ldh Synthesized By Mechanochemistrymentioning
confidence: 99%